Resisting the Inevitable: Tar Sands, Regionalism and Rhetoric - Steven M. Hoffman; Paul Lorah; Joseph Janochoski (European Journal of American Studies)
Tar sands oil is rapidly becoming a primary means of powering the world’s petroleum-based economy. Despite some formidable barriers, an oppositional network is developing that spans the North American continent. This paper discusses the diverse nature of this opposition through an examination of 26 collective activities involving some 243 organizations. The first part of the analysis discusses the internal characteristics and the network dynamics of these activities; this is followed by a spatial analysis of the relationships among the participant organizations. The final section of the paper suggests that an important mechanism for achieving collaborative integrity in the midst of what are oftentimes very challenging circumstances are carefully elaborated rhetorical frames designed to appeal to a diverse set of key stakeholders and policymakers.